Improving the Ability of Representation and Problem Solving Through Concrete Representational Abstract (CRA) Approach in Mathematical Learning - Zulfakri, Zulfakri; Ikhsan, M.; Yusrizal, Yusrizal (Universitas Malikussaleh, 2019)
The representation and mathematical problem-solving abilities of students are still relatively low. The low ability is due to the lack of attention of the implementers of learning to develop learning that can improve the ability of representation and mathematical problem-solving. One effort that can be done is to apply to learn through the Concrete Representational Abstract (CRA) approach. This study aims to analyze the increase in representation ability and mathematical problem solving of students and to examine the interaction between student learning and the ability of representation and mathematical problem solving of students. This research is quantitative research with an experimental method with the design of the pretest-posttest group design. The population of this study was all students of SMP Negeri 1 Banda Aceh with a sample of two classes which became the experimental and control classes. The instrument of data collection is a test of representation ability and mathematical problem-solving. Data analysis of the study was carried out with SPSS 23 assisted two-way ANOVA for windows at a significant level of 0.05. The results of the study showed that: 1) the improvement of the representation and mathematical problem-solving abilities of students who obtained learning through the CRA approach was better than improving the problem-solving abilities of students who obtained conventional learning 2) there was no interaction between the CRA approach and the student level towards improving representation and solving abilities mathematical problem